KEKACAUAN PEMILU 2019: FENOMENA FIREHOSE OF FALSEHOOD DALAM RELASI SIKAP TERHADAP HOAX DAN KEPERCAYAAN MASYARAKAT TERHADAP KOMISI PEMILIHAN UMUM - Akhrani, Lusy Asa; Herani, Ika; Pohan, Ibnu Asqori; Alhad, Muhammad Afif (Faculty of Social and Political Science Universitas Brawijaya, 2020)
Firehose of falsehood is a propaganda technique that has used in the political world. This propaganda is used by presenting hoax news/hoaxes in public awareness continuously until the public believes the news. The community more easily and quickly accepts media news anywhere and anytime because the public has direct media access to grasp. In contrast, the literacy and rechecking of news content are often not done due to time constraints and the emotional content of newsreaders. Information media believed to be one of the sources of increasing distrust in the election organizers, namely the KPU. This study aims to explore people's attitudes towards HOAX news on trust in the KPU. The research method uses quantitative with a survey approach to 558 2019 voter respondents through the distribution of Trust research scale to KPU and attitude scale towards hoaxes. The results study indicate there is a role for attitudes towards hoaxes towards trust in the KPU as an EMB in Indonesia.